Phf8 histone demethylase deficiency causes cognitive impairments through the mTOR pathway - Xuemei Chen (Nature Portfolio, 2018)
Mutations in PHF8 gene are genetically associated with X-linked mental retardation. Here, Chen et al. show that Phf8 KO mouse have cognitive and synaptic plasticity impairment, and pharmacological inhibition of mTOR signaling can partially alleviate such defects.